2022
DOI: 10.1186/s13256-022-03296-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in hereditary hemorrhagic telangiectasia associated with ACVRL1 mutation: a case report

Abstract: Introduction Hereditary hemorrhagic telangiectasia is an autosomal dominant condition with an estimated prevalence of 1 in 5000. It is characterized by the presence of abnormalities of vascular structures, and may affect many organ systems, including the lungs, brain, spinal cord, gastrointestinal tract, and liver. A causative mutation is identified in approximately 97% of patients with definite hereditary hemorrhagic telangiectasia in one of three genes including a mutation in endoglin, a muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Variant p.Arg484Gln impacts a conserved surface-exposed residue located in helix αI of the kinase C-lobe, and encodes a catalytically inactive ALK1 mutant 86 . Mutations in this region are associated with HHT2, an increased incidence of pulmonary arterial hypertension [87][88][89] , and with other ALK family-associated diseases such as brachydactyly type A2 (ALK6) 90,91 and Loeys-Dietz syndrome (ALK5) 92,93 . ACVRL1 p.Arg484Gln has also been identified in HHT2 94 and in childhood-onset pulmonary arterial hypertension 95 .…”
Section: Variants In Acvrl1 and Other Mutation-intolerant Mendelian V...mentioning
confidence: 99%
“…Variant p.Arg484Gln impacts a conserved surface-exposed residue located in helix αI of the kinase C-lobe, and encodes a catalytically inactive ALK1 mutant 86 . Mutations in this region are associated with HHT2, an increased incidence of pulmonary arterial hypertension [87][88][89] , and with other ALK family-associated diseases such as brachydactyly type A2 (ALK6) 90,91 and Loeys-Dietz syndrome (ALK5) 92,93 . ACVRL1 p.Arg484Gln has also been identified in HHT2 94 and in childhood-onset pulmonary arterial hypertension 95 .…”
Section: Variants In Acvrl1 and Other Mutation-intolerant Mendelian V...mentioning
confidence: 99%
“…Beyond supportive therapy (e.g., oxygen supplementation, diuretics, and iron replacement), the treatment of PAH in patients with HHT currently involves the use of standard PAH vasodilator therapies, including endothelin receptor antagonists, phosphodiesterase inhibitors, soluble guanylate cyclase stimulators, and prostanoids. Individual studies have reported success, either in normalization of hemodynamic parameters or improvement of functional status, with the use of bosentan, sildenafil, selexipag, epoprostenol, treprostinil, and iloprost 81–87 . One investigation included a cohort of five patients as well as an analysis of 32 subjects across 21 studies, all of whom were patients with HHT and PAH treated with oral or intravenous prostanoids 87 .…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Individual studies have reported success, either in normalization of hemodynamic parameters or improvement of functional status, with the use of bosentan, sildenafil, selexipag, epoprostenol, treprostinil, and iloprost. 81 , 82 , 83 , 84 , 85 , 86 , 87 One investigation included a cohort of five patients as well as an analysis of 32 subjects across 21 studies, all of whom were patients with HHT and PAH treated with oral or intravenous prostanoids. 87 Results showed significant improvement in mPAP (65 ± 19 pretreatment vs. 51 ± 16 mmHg posttreatment; p = 0.04) and PVR (12 ± 6 pretreatment vs. 8 ± 4 WUs posttreatment; p = 0.01) following therapy, with no significant difference in survival between those who received oral or intravenous medication.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Interestingly, a few HHT individuals carrying ACVRL1 mutations are predisposed to the development of PAH [227]. Currently, in those ACVR1L mutant affected HHT2 patients, PAH is seen as an extremely rare complication [228]. Similarly, GDF2 mutations cause a vascular-anomaly syndrome somehow overlapping with HHT [205], and some BMPR2 variants increase the risk of developing pulmonary AVMs reminiscent of an HHT-like condition [229].…”
Section: Hereditary Haemorrhagic Telangiectasia and Hipscsmentioning
confidence: 99%